The psychological foundations of culture - Schaller, Mark, 1962-; Crandall, Christian S., 1959- (Mahwah, N.J. : Lawrence Erlbaum, 2004)
How is it that cultures come into existence at all? How do cultures develop particular customs and characteristics rather than others? How do cultures persist and change over time? Most previous attempts to address these questions have been descriptive and historical. The purpose of this book is to provide answers that are explanatory, predictive, and relevant to the emergence and continuing evolution of cultures past, present, and future. Most other investigations into ""cultural psychology"" have focused on the impact that culture has on the psychology of the individual. The focus of this bo.
Part INTRODUCTION -- chapter 1 The Psychological Foundations of Culture: An Introduction / Mark Schaller -- part PART I: HOW CULTURES EMERGE AT ALL -- chapter 2 Human Awareness of Mortality and the Evolution of Culture / Sheldon Solomon -- chapter 3 Cultural Elements Emerge From Dynamic Social Impact / Helen C. Harton -- chapter 4 Language, Cognition, and Reality: Constructing Shared Meanings Through Communication / Ivy Y.-M. Lau, Sau-lai Lee, and Chi-yue Chiu -- chapter 5 Motivated Closed Mindedness and the Emergence of Culture / Linda Richter -- part PART II: HOW SPECIFIC CULTURAL NORMS ARISE -- chapter 6 Biological Foundations of Moral Norms / Dennis Krebs -- chapter 7 Cognitive and Emotional Processes in the Cultural Transmission of Natural and Nonnatural Beliefs / Ara Norenzayan -- chapter 8 Self-Organizing Culture: How Norms Emerge in Small Groups / Holly Arrow -- chapter 9 Scientists and Science: How Individual Goals Shape Collective Norms / Christian S. Crandall -- part PART III HOW CULTURES PERSIST AND CHANGE OVER TIME -- chapter 10 The Microgenesis of Culture: Serial Reproduction as an Experimental Simulation of Cultural Dynamics / Allison McIntyre -- chapter 11 Sustaining Cultural Beliefs in the Face of Their Violation: The Case of Gender Stereotypes / Deborah A. Prentice -- chapter 12 When Believing Is Seeing: Sustaining Norms of Violence in Cultures of Honor / Joseph A. Vandello -- chapter 13 Move the Body, Change the Self: Acculturative Effects on the Self-Concept -- part EPILOGUE -- chapter 14 Toward a Conception of Culture Suitable for a Social Psychology of Culture / Glenn Adams.
Includes bibliographical references and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Social change -- Psychological aspects; Culture -- Origin -- Psychological aspects; Ethnopsychology; Ethnopsychology; Changement social -- Aspect psychologique; Culture -- Origines -- Aspect psychologique; Ethnopsychologie; ethnopsychology; SOCIAL SCIENCE -- Anthropology -- Cultural; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Popular Culture; Culture -- Origin -- Psychological aspects; Ethnopsychology; Social change -- Psychological aspects; Ethnopsychology; Social change -- Psychological aspects; Kulturpsychologie; Ethnopsychologie; Soziokultureller Wandel; Cultuurpsychologie